Ti-Ta multilayer film with gradient structure and preparation method thereof
By preparing Ti-Ta multilayer thin films with gradient structures and controlling the gradual change in film thickness using magnetron sputtering, the problem of insufficient mechanical properties of Ti-Ta alloy nanolayer films was solved, and the application of thin films with high hardness and high elastic modulus was realized.
Patent Information
- Application Number
- CN202310881547.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-07-18
AI Technical Summary
The mechanical properties of existing Ti-Ta alloy nanolayer films have not reached the ideal level, especially in terms of high wear resistance and high hardness. Moreover, the simple structure of nanolayer films makes it difficult to meet the service requirements in harsh environments.
Ti-Ta multilayer thin films with gradient structures were prepared by magnetron sputtering. By alternately stacking Ti and Ta thin film layers and controlling the gradual change in the thickness of each layer, the Ta thin film layer gradually increased while the Ti thin film layer gradually decreased, forming a tightly bonded multilayer structure.
It significantly improves the hardness and elastic modulus of Ti-Ta multilayer films, enhances the strength and deformation resistance of the films, and is suitable for protective coatings and tool coatings.
Smart Images

Figure CN117026163B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of metal material coating with at least two superimposed layers obtained by sputtering method, and particularly relates to a Ti-Ta multilayer film with gradient structure and a preparation method thereof. BACKGROUND
[0002] To meet the needs of modern development, it is urgent to develop new materials to meet the service conditions in harsh environments (such as high wear resistance, high hardness and ductility, etc.). In recent years, nano-multilayer films have been applied in the field of tool coating due to the strong Hall-Petch effect of their fine crystals, but due to their single structure, only two components are alternately superimposed together in constant or irregular proportions, and the mechanical properties cannot reach the ideal height. The elastic modulus of the Ti-Ta alloy prepared in patent CN104342583A can only reach 50-70GPa.
[0003] In order to improve the mechanical properties of Ti-Ta system, the application designs and prepares a Ti-Ta multilayer film with gradient structure in the form of double-component thickness gradient, which has ultra-high hardness and elastic modulus, the hardness is as high as 6.75GPa, and the elastic modulus is as high as 92.56GPa, which significantly improves the mechanical properties of Ti-Ta film. SUMMARY
[0004] The technical problem to be solved by the application is to provide a Ti-Ta multilayer film with gradient structure and a preparation method thereof to solve the above problems in the prior art. The Ti-Ta multilayer film with gradient structure has ultra-high hardness and elastic modulus, and can be applied in the field of protective coating and tool coating.
[0005] To solve the above technical problems, the technical scheme provided by the application is:
[0006] A Ti-Ta multilayer film with gradient structure is provided, which is obtained by alternately superimposing Ti film layers and Ta film layers on a Ta substrate material. The Ta film layer is in direct contact with the Ta substrate material, and the thickness of the Ta film layer gradually increases in order from top to bottom, and the thickness of the Ti film layer gradually decreases in order.
[0007] According to the above scheme, the Ta substrate material is a pure metal Ta sheet with a purity of 99.99wt% or more and a thickness of 0.1-1mm.
[0008] According to the above scheme, the Ti film layer and the Ta film layer are prepared by a magnetron sputtering method.
[0009] According to the above scheme, the total thickness of the Ti film layer and the Ta film layer covering the surface of the Ta substrate material is 1.8-6μm.
[0010] According to the above scheme, the total thickness of all Ti film layers is 0.9-3 microns, the thinnest Ti film layer is 1-15 nm thick, the thickest Ti film layer is 100-300 nm thick, and the thickness difference between two adjacent Ti film layers is 5-20 nm.
[0011] According to the above scheme, the total thickness of all Ta film layers is 0.9-3 microns, the thinnest Ta film layer is 5-15 nm thick, the thickest Ta film layer is 100-330 nm thick, and the thickness difference between two adjacent Ta film layers is 5-20 nm.
[0012] The application also includes a preparation method of the Ti-Ta multilayer film with a gradient structure as described above, and the specific steps are as follows:
[0013] 1) A non-equilibrium magnetron sputtering device is used for deposition, a Ti target and a Ta target with the same size are respectively installed on two cathode arc targets in the deposition cavity of the magnetron sputtering device, the target surfaces of the Ti target and the Ta target are both directed towards the sample table, and the target surfaces and the sample table form an angle of 45°;
[0014] 2) A clean substrate material is placed at the center of the sample table, the sample table is self-rotated at a speed of 10-20 r / min, and the deposition cavity is vacuumed to 8.5*10 -4 ~ 1.2*10 -3 Pa;
[0015] 3) Argon gas is introduced into the deposition cavity, the deposition pressure is adjusted to 1.5-2.0 Pa, the deposition temperature is 20-100℃, the power supply of the Ti target and the Ta target is turned on alternately, a Ta film layer is first deposited, then Ti film layers and Ta film layers are alternately deposited in sequence, the deposition time of each film layer is controlled to gradually and orderly reduce the thickness of the deposited Ta film layers and gradually and orderly increase the thickness of the Ti film layers, and a Ti-Ta multilayer film with a gradient structure is obtained on the surface of the substrate material after deposition.
[0016] According to the above scheme, the purity of the Ti target and the Ta target in step 1) is above 99.9 wt%.
[0017] According to the above scheme, the distance between the Ti target and the Ta target and the sample table in step 1) is 140-180 mm.
[0018] According to the above scheme, the purity of the argon gas in step 3) is above 99.9 vol%, and the argon gas flow is 20-40 sccm.
[0019] According to the above scheme, the Ti target sputtering power in step 3) is 80-100 W, the single sputtering time is 0.5-30 min, the Ta target sputtering power is 80-100 W, and the single sputtering time is 0.5-30 min.
[0020] The application of the Ti-Ta multilayer film with gradient structure in the field of protective coating and tool coating.
[0021] The Ti-Ta multilayer film with gradient structure provided by the application has the advantages that the Poisson ratio mismatch at the interfaces of each layer film caused by the unevenness of the thickness of the two components causes mechanical incompatibility, and then causes dislocations to accumulate each other at the interfaces, thereby causing the strength to be improved; in addition, the gradually changing gradient structure of the thickness of each component changes the stress propagation time in each layer when the film is subjected to external force, so that the stress is effectively transferred and slowly released, that is, the stress action strength is slowed down, so that the film strength is improved; when subjected to external force to produce strain, the film with gradient structure generates a stress gradient in the layer, causing the dislocation density between the layers to be arranged in a gradient, thereby further improving the strength.
[0022] The application adopts a magnetron sputtering device to prepare the Ti-Ta multilayer film with gradient structure in an alternating and continuous film plating form, gradually changes the thickness of each metal layer in the structure design to realize the ordered and continuous change of the components, and prepares the Ti-Ta multilayer film with tight interlayer bonding and super-high hardness and elastic modulus.
[0023] The application has the advantages that: 1. The Ti-Ta multilayer film with gradient structure provided by the application has obvious gradient structure, tight interlayer bonding, no obvious gap in the thickness direction of the film, super-high hardness and elastic modulus, and can be used in the fields of coating protection and tools; 2. The application has simple process, good controllability and repeatability, and is convenient for large-scale production. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 The structure schematic diagram of the Ti-Ta multilayer film prepared in embodiment 1 of the application;
[0025] Figure 2 The cross-section scanning electron microscope graph of the Ti-Ta multilayer film prepared in embodiment 1;
[0026] Figure 3 The cross-section EDS line scanning and element content graph of the Ti-Ta multilayer film prepared in embodiment 1;
[0027] Figure 4 The scanning electron microscope graph of the surface of the Ti-Ta multilayer film prepared in embodiment 1;
[0028] Figure 5 The X-ray diffraction spectrum graph of the Ti-Ta multilayer film prepared in embodiment 1;
[0029] Figure 6 The atomic force microscope spectrum graph of the Ti-Ta multilayer film prepared in embodiment 1;
[0030] Figure 7 Nanoindentation test graph of the Ti-Ta multilayer film prepared in Example 1;
[0031] Figure 8 Hardness and elastic modulus at different positions of the Ti-Ta multilayer film prepared in Example 1. DETAILED DESCRIPTION
[0032] In order for those skilled in the art to better understand the technical solutions of the present application, the present application will be further described in detail below with reference to the drawings.
[0033] Example 1
[0034] A Ti-Ta multilayer film with a gradient structure is prepared by the following method:
[0035] 1) Two metal Ta and Ti targets of the same specification (diameter 50.8 mm, thickness 4 mm, purity 99.9 wt%) are installed on two target positions of a non-equilibrium magnetron sputtering film coater, and the target surface and sample stage angle is adjusted to 45°, and the distance between the two target surfaces and the sample stage is 140 mm;
[0036] 2) A pure metal Ta sheet (10 mm x 10 mm x 1 mm, purity 99.99 wt%) is selected as the substrate material, the substrate is polished with sandpaper, then immersed in hydrochloric acid (concentration 0.8 mol / L) for 8 h, and then sequentially ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 30 min each, and then dried with a nitrogen gun after ultrasonic cleaning;
[0037] 3) The cleaned substrate material is then placed on a sample stage with a rotating turret, and the cavity is vacuumed to 1.2 x 10 -3 Pa at 25℃, and the sample stage is revolved at a rate of 10 r / min;
[0038] 4) The argon gas path is opened, 20 sccm of argon gas (purity 99.9 vol%) is introduced into the chamber, and the argon partial pressure is adjusted to maintain 1.5 Pa, the Ta target power supply is turned on, the target sputtering power is set to 80 W, and sputtering is performed for 19 min as the bottom layer, then the Ta target power supply is turned off, the Ti target power supply is turned on, the target sputtering power is set to 80 W, and sputtering is performed for 1 min, then the Ti target power supply is turned off, the Ta target power supply is turned on, the target sputtering power is set to 80 W, and sputtering is performed for 18 min, then the Ta target power supply is turned off, the Ti target power supply is turned on, the target sputtering power is set to 80 W, and sputtering is performed for 2.1 min;
[0039] 5) According to the rule described in step 4), the power supply of the Ti target and the Ta target is turned on alternately, the sputtering time of the Ta target is reduced by 1 min per layer, and the sputtering time of the Ti target is increased by 1.1 min correspondingly, until the sputtering time of the Ta target is 1 min and the sputtering time of the Ti target is 20.8 min, and then the sputtering is stopped, and finally a Ti-Ta multilayer film with a gradient structure is obtained on the surface of the substrate material. Taking a Ta layer and an adjacent Ti layer on the top as a Ti-Ta bilayer, a Ti-Ta metal film with a gradient structure of 19 Ti-Ta bilayers is finally obtained.
[0040] Figure 1 A schematic diagram of the structure of the Ti-Ta multilayer film with a gradient structure prepared in this embodiment, in which the thickness of the Ta layer gradually decreases from bottom to top, and the thickness of the Ti layer gradually increases.
[0041] Figure 2 A scanning electron microscope image of the cross section of the Ti-Ta multilayer film with a gradient structure prepared in this embodiment, in which the brighter part is the Ta layer and the darker part is the Ti layer. It can be seen from the scanning electron microscope image that the multilayer alternating film with a gradient structure is successfully prepared in this embodiment, and the film layers are closely connected. The thickness of a Ti-Ta bilayer is about 210-260 nm, and the total thickness of the Ti-Ta multilayer film on the surface of the substrate material is 3.97 μm. The total thickness of all Ti film layers is 1.95 μm, the thinnest Ti layer is 9 nm thick, the thickest Ti layer is 220 nm thick, and the difference in thickness between two adjacent Ti film layers is about 10 nm. The total thickness of all Ta film layers is 2.02 μm, the thinnest Ta layer is 11 nm thick, the thickest Ta layer is 210 nm thick, and the difference in thickness between two adjacent Ta film layers is 11 nm.
[0042] Figure 3 A cross-sectional EDS line scan and element content diagram of the Ti-Ta multilayer film prepared in this embodiment. It can be seen that the contents of Ta and Ti show a regular gradient change, the content of Ta gradually decreases along the thickness direction, the content of Ti gradually increases along the thickness direction, and the atomic number contents of the two are close to 1:1, indicating that the layer thickness control is relatively accurate.
[0043] Figure 4 A scanning electron microscope image of the surface of the Ti-Ta multilayer film prepared in this embodiment. It can be seen that the micro-particles of the film show a flaky shape, and no obvious pores are observed on the surface, indicating that the film grows closely.
[0044] Figure 5 An X-ray diffraction spectrum of the Ti-Ta multilayer film prepared in this embodiment. It can be seen from the figure that the deposited Ta layer and Ti layer are both body-centered cubic structure, which is fcc / fcc type, and the preferred orientation is <110>, and the film has good crystallinity, and the peak positions are consistent.
[0045] Figure 6 The atomic force microscope spectrum of the Ti-Ta multilayer film prepared in the example is shown in the figure. It can be seen from the figure that the film surface is relatively smooth, the particles grow uniformly, and the roughness is 35.4 nm.
[0046] Figure 7 The loading-unloading curves of the Ti-Ta multilayer film prepared in the example at 10 mN load at four different points on the surface are shown in the figure. It can be seen from the figure that the loading-unloading curves of the four different positions almost overlap, indicating that the gradient film has good bearing capacity and strong elastic recovery force.
[0047] Figure 8 The hardness and elastic modulus change curves of the Ti-Ta multilayer film prepared in the example at 10 mN load at four different positions on the surface can be seen. The hardness of the gradient film at different positions is uniform, the average hardness is 6.75 GPa, and the highest reaches 7.63 GPa, indicating that the gradient structure of the film gives the nano-multilayer film super-high hardness, the average elastic modulus is 92.56 GPa, and the maximum elastic modulus is 101.34 GPa, indicating that the gradient structure of the film has strong anti-deformation ability.
Claims
1. A Ti-Ta multilayer film having a gradient structure, characterized by, The Ti-Ta multilayer film with gradient structure is obtained by alternately stacking Ti film layers and Ta film layers on a Ta substrate material, and the Ta film layer in direct contact with the Ta substrate material has a gradually ordered increase in thickness from top to bottom, and the Ti film layer has a gradually ordered decrease in thickness from top to bottom; The total thickness of all the Ti film layers is 0.9-3 μm, the thinnest Ti film layer has a thickness of 1-15 nm, the thickest Ti film layer has a thickness of 100-300 nm, and the difference in thickness between two adjacent Ti film layers is 5-20 nm; The total thickness of all the Ta film layers is 0.9-3 μm, the thinnest Ta film layer has a thickness of 5-15 nm, the thickest Ta film layer has a thickness of 100-330 nm, and the difference in thickness between two adjacent Ta film layers is 5-20 nm.
2. The Ti-Ta multilayer film having a gradient structure according to claim 1, characterized by, The Ta substrate material is a pure Ta sheet with a purity of 99.99 wt% and a thickness of 0.1-1 mm.
3. The Ti-Ta multilayer film having a gradient structure according to claim 1, characterized by, The Ti film layers and the Ta film layers are prepared by a magnetron sputtering method.
4. The Ti-Ta multilayer film having a gradient structure according to claim 1, characterized by, The total thickness of the Ti film layers and the Ta film layers on the surface of the Ta substrate material is 1.8-6 μm.
5. A method of producing the Ti-Ta multilayer film having a gradient structure according to any one of claims 1 to 4, characterized by, The specific steps are as follows: 1) A non-equilibrium magnetron sputtering device is used for deposition, a Ti target and a Ta target with the same size are respectively installed on two cathode arc targets in the deposition cavity of the magnetron sputtering device, the target surfaces of the Ti target and the Ta target are both directed towards the sample table, and the target surfaces and the sample table form an angle of 45°; 2) Put the cleaned substrate material in the center of the sample stage, the sample stage rotates at a speed of 10~20r / min, the deposition cavity is pumped to 8.5×10 -4 ~1.2×10 -3 Pa; 3) Argon gas is introduced into the deposition cavity, the deposition gas pressure is adjusted to 1.5-2.0 Pa, the deposition temperature is 20-100 ℃, the power supply of the Ti target and the Ta target is turned on alternately, a Ta film layer is first deposited, then Ti film layers and Ta film layers are alternately deposited in sequence, the deposition time of each film layer is controlled to make the thickness of the deposited Ta film layers gradually ordered decrease and the thickness of the Ti film layers gradually ordered increase, and a Ti-Ta multilayer film with gradient structure is obtained on the surface of the substrate material after deposition.
6. The method of claim 5, wherein the Ti-Ta multilayer film having a gradient structure is prepared by the steps of: depositing a Ti layer on a substrate; and depositing a Ta layer on the Ti layer. The purity of the Ti target and the Ta target in step 1) is more than 99.9 wt%, and the distance between the Ti target and the Ta target and the sample table in step 1) is 140-180 mm.
7. The method of claim 5, wherein the Ti-Ta multilayer film having a gradient structure is prepared by the steps of: depositing a Ti layer on a substrate; and depositing a Ta layer on the Ti layer. The purity of the argon gas in step 3) is more than 99.9 vol%, and the argon gas flow is 20-40 sccm; the sputtering power of the Ti target in step 3) is 80-100 W, the single sputtering time is 0.5-30 min, the sputtering power of the Ta target is 80-100 W, and the single sputtering time is 0.5-30 min.
8. Application of the Ti-Ta multilayer film with gradient structure in the field of protective coatings according to any one of claims 1-4.
Citation Information
Patent Citations
Ti-Ta alloy as well as preparation method and application thereof
CN104342583A
Method for improving toughness of nano-metal multilayer film
CN111020513A
Titanium-tantalum laminated composite adopting gradient structure and preparation method of titanium-tantalum laminated composite
CN111569155A